MORPHOLOGICAL, AGRONOMIC, AND QUALITY PROPERTIES OF THE TWO DEVELOPED POPULATIONS OF ALFALFA (Medicago sativa L.) UNDER NON-IRRIGATED CONDITIONS OF SEMIARID REGIONS - Unal, Sabahaddin; Efe, Berna; Mutlu, Ziya; Isik, Saban; Mintas, Hacer; Oral, Hulya Hanoglu (Soc Field Crop Sci, 2023)
Alfalfa is the most important forage crop in Turkey, but no alfalfa cultivar has been developed for non-irrigated conditions in the semiarid regions of Turkey. Hence, new cultivars are needed for using in rangeland improvement, artificial pasture establishment, and hay production. The two populations (L-533, and L-1739) were compared with the three control cultivars of alfalfa (Bilensoy-80, Savas and Kayseri) in two various regions of Turkey during two years. The general results showed that there were significant differences in the plant height, but no differences in stem diameter, and stem numbers among the studied genotypes. According to combined analysis results, the L-533 and Kayseri had the highest green and hay yields, but the Savas cultivar had the lowest. Moreover, as compared to the Bilensoy-80 cultivar, the L-533 and L-1739 populations produced higher green forage yields of 22.27 and 11.57%, respectively. Also, the same increase in hay yield was 18.30% and 10.13%, respectively. Excluding crude protein contents, there were statistical differences between genotypes for the acid detergent fiber, neutral detergent fiber, and digestible dry matter yield. Moreover, higher crude protein content and digestible dry matter yield were obtained from the L-533 and L-1739, but the L-533 had also the lowest neutral detergent fiber content relative to the other population, and cultivars. The results of the current study have demonstrated that the L-533, and L-1739 had high adaptation capability, yields, and quality performance under dryland conditions of a semi-arid region and could be used as commercial cultivars.
Keywords: Advanced population; alfalfa; crude protein; dry forage; green forage